Situation Report: Hungary, 12 January 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungary's 1971 Budget Sino-Hungarian Trade and the Statistical Yearbook Reaction to Polish Events Illyes Argues Small Nations' Future Is in Danger Stagnation in Development of Private Plot Farming A Joint Enterprise to Break the State's Trade Monopoly Co-opturist [Cooptourist] Program for 1971